Direct Instruction: Strategi Pembelajaran Efektif Di Era Digital: (Menyoroti Relevansi Model DI Di Jaman Modern) Mata Kuliah Aransemen Paduan Suara - Ance Juliet Panggabean; Junita Batubara; Ronald Heriko Saragih; Romahulina Saragih (Journal of Music Science, Technology, and Industry, 2025)
Purpose: This study implements digital technology through the Song Maker application as a learning medium in elementary school music education. The purpose of this study is to describe the application of Song Maker in improving students' musicality, particularly their ability to understand melody, harmony, and create simple musical works. The study employed a classroom action research method with a mixed-methods approach, involving four fourth-grade students from SD Galenia Bandung. Research method: Data were collected through observation, interviews, questionnaires, and documentation. Results and discussion: The results showed a significant improvement in students' musical understanding and engagement after the implementation of Song Maker. Students were better able to recognize melodies and harmonies, more active in music learning, and successfully composed simple musical works. Implication: These findings demonstrate that interactive digital media provide meaningful and enjoyable learning experiences while enhancing students' cognitive and creative aspects. The integration of Song Maker as a digital learning medium is effective in fostering musicality among elementary school students and provides important insights for future innovations in music education.